2018
DOI: 10.1371/journal.pone.0191830
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses following Kawasaki disease and toxic shock syndrome

Abstract: The pathogenesis of Kawasaki disease (KD) remains unknown and there is accumulating evidence for the importance of the innate immune system in initiating and mediating the host inflammatory response. We compared innate immune responses in KD and toxic shock syndrome (TSS) participants more than two years after their acute illness with control participants to investigate differences in their immune phenotype. Toxic shock syndrome shares many clinical features with KD; by including both disease groups we endeavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…It is noteworthy that the innate immune system has an important role during the acute phase of KD . There are some complement‐related proteins such as C3, C4 and complement factor H (CFH), overlapped.…”
Section: Evs Proteomics In Cardiovascular Diseasementioning
confidence: 99%
“…It is noteworthy that the innate immune system has an important role during the acute phase of KD . There are some complement‐related proteins such as C3, C4 and complement factor H (CFH), overlapped.…”
Section: Evs Proteomics In Cardiovascular Diseasementioning
confidence: 99%
“…The aetiological mechanism of KD remains unclear and the causal factors are also unknown (6). Although there is no definitive evidence that KD is an infectious disease, recent studies support the view that a dysregulated immune response to a variety of infectious stimuli is likely to contribute to KD pathogenesis (6,7). Based on these studies, this short review explores the possible relationship between KD and the immune response to various infectious agents (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that immune activation and secretion of various cytokines play a key role in the pathogenesis of KD by mediating the imbalance of proinflammatory and anti-inflammatory responses. A variety of proinflammatory and anti-inflammatory cytokines have been reported to increase significantly during acute KD, such as IL-1 , TNF-α , IL-6 , IL-8 , and IL-10 [12–14]. These proinflammatory cytokines induce endothelial cell apoptosis, which is the cause of vascular endothelial injury in KD and has been implicated in the development of the disease [1517].…”
Section: Introductionmentioning
confidence: 99%